Sorting lines as an element of household waste management at the regional level - Holik , Yurii; Illiash, Oksana; Serha, Tetiana; Chepurko, Iuliia (Academic journal Industrial Machine Building Civil Engineering, 2024)
The article identifies the problems of household waste recycling, summarizes the data on the planned waste management infrastructure facilities, and substantiates the feasibility of building waste treatment facilities in Poltava region. The absence of a recycling system (including a separate collection system) for household waste results in Ukraine losing millions of tons of resource materials contained in waste that could potentially be put back into economic circulation. It has been established that sorting mixed household waste will enable its further reuse and recovery and reduce the load on landfills. It is determined that the stage of sorting (separation) of household waste is an integral part of integrated waste management solutions and, accordingly, is a mandatory stage before further application of waste treatment technologies